Erich fromm and global public sociology - Mclaughlin, Neil (UK Bristol university press, 2023)
As the rise of global right-wing populism and Trumpism creates new interest in psycho-social writing and popular sociology, this timely book tells the story of the rise, fall and contemporary revival of the theories of Erich Fromm, a 1930s influential and creative public intellectual.
Keywords: Sociology: General Interest; Sociology; History of the Social and Behavioral Sciences